Evaluating Nurses Knowledge, Misconceptions, and Attitudes Towards Treating Patients with Chronic Pain - Burton, Richard; Judson, Holly (Babali Nursing Research, 2024)
Introduction: Chronic pain is complex biopsychosocial phenomenon that affects people worldwide, and nurses play a vital role in treatment. It is essential for nurses to have adequate knowledge and demonstrate no bias towards these patients. Aims: Determine nurses’ knowledge and attitudes regarding any patients with pain. Identify any potential biases. Methods: The knowledge and attitudes of registered nurses regarding pain were assessed using (KAS survey). A convenience sample was chosen. Data was analyzed to determine knowledge and attitudes regarding treating patients with chronic pain. Results: 55.5% of participants demonstrated “good knowledge and attitudes”, while 44.0% participants had “acceptable knowledge and attitudes”. There was no significant correlation between years’ experience and test scores. There was a statistical difference between genders in relation to dependent variable test score. Conclusions: Participants demonstrated higher knowledge than previous works. Data revealed participants did not hold any biases or misconceptions about treating patients with chronic pain.